Cationic indenylnickel complexes bearing a 1, 5-cyclooctadiene ligand: Synthesis and characterization. (25th September 2016) - Gomes, Clara S.B.; Costa, Sandra I.; Veiros, Luís F.; Gomes, Pedro T.
Graphical abstract: The stoichiometric protonation of [Ni(η-1-R-Ind)2 ] (R = H, Me) with HBF4 in the presence of one equivalent of 1, 5-cyclooctadiene, at low temperature, afforded the corresponding cationic complexes [Ni(η-1-R-Ind)(η 4 -COD)]BF4 in very high yields. Their X-ray diffraction and NMR characterization is presented. Abstract: The reaction of [Ni(η-1-R-Ind)2 ] (R = H, Me) with one equivalent of 1, 5-cyclooctadiene (COD), in the presence of a stoichiometric amount of HBF4 (in Et2 O), at low temperature, afforded the corresponding cationic [Ni(η-1-R-Ind)(η 4 -COD)]BF4 in high yields. In the solid state, these complexes showed a slightly distorted pseudo-square-planar geometry around the metal centre. In solution, 1 H NMR spectra showed the existence of a fluxional process involving the 1, 5-cyclooctadiene ligand. This process was investigated by DFT calculations and the results exclude the possibility of η 5 -indenyl rotation.